Post-Graduation Plans of International Science and Engineering Doctoral Students Attending U.S. Universities - Ugwu, Dorothy N.; Adamuti-Trache, Maria (Journal of International Students, 2017)
This study examines the post-graduation plans of international science and engineering doctoral students at a public research-intensive university, and the extent to which graduate school experiences influence post-graduation plans. The study is grounded in Tinto’s Integration Model as well as Berry’s Acculturation Model. Study findings highlight the variety of challenges international doctoral students go through such as adapting to a new culture, experiencing English language difficulties, and cultural, social, and academic adjustment barriers. Using survey data collected in 2013-2014, this study reveals the complexity of factors that affect post-graduation plans and need for institutional initiatives to provide socio-cultural and academic support, and recommends changes in immigration policies to sustain the retention of talented international scientists and engineers upon degree completion.